Tempo de tela e coordenação motora grossa: um estudo com crianças - Mednis, Lucas (2021)
The time spent on sedentary behavior has been increasing in children. Studies have linked high screen time with worse levels of physical fitness, physical activity and health status. Sedentary behavior can limit the experience of motor tasks and reduce levels of motor coordination. The aim of this study is to test the association between screen time and motor coordination in children. This is a cross-sectional school-based study in which 1,607 children (848 girls) participated, aged between five and 11 years, from the city of São José dos Pinhais, Paraná́ . Screen time was assessed by a questionnaire (self-reported) answered with the help of those responsible. Answers were categorized into: do not use devices; meet the recommendations (use up to two hours a day); exceed the recommendations (they use more than two hours a day). Gross motor coordination was evaluated with the KTK test battery (KörperKoordinationstest für Kinder) to obtain the motor quotient. Individual variables (height and body mass) were evaluated and, for physical fitness, the cardiorespiratory endurance tests (6min run), muscle strength (grip and horizontal jump), agility and speed (shuttle running and 20m run) were applied. The global fitness score. Sport participation was raised by questionnaires. Differences in coordination performance between sexes were tested with the t test for independent samples, and between screen time categories with analysis of variance. Linear regression models were built to test the associations between screen time and gross motor coordination, with adjustment for age, gender, BMI, physical fitness levels and sports practice. Statistics were performed using SPSS software version 27.0, keeping the significance level at 5%. Girls were less coordinated than boys. Motor quotient values seem to decrease with age, and older children have a higher prevalence of coordination problems. Children with higher BMI values are less coordinated (β = 0.09; p < 0.001). Children who practice physical activity (β = 0.05; p < 0.001) and the fittest (β = 0.47; p < 0.001) are more coordinated. Children who spend more time using the computer have less gross motor coordination (β = -0.04; p = 0.014). No relationships were found between television time, mobile devices and videogames and motor coordination. Computer use is inversely associated with motor coordination. Decreased computer use or/or substitution for physical activities can improve motor coordination levels.